A reprodução do preconceito de gênero no discurso das assistentes virtuais - Oliveira, Christiane Burle de (2022)
Virtual assistants use to be presented by default with a female name and voice. The studies of Science, Technology and Society (STS) refers to a technology that is not neutral. In this work, it is analyzed the reproduction of gender bias in the discourse of Alexa, Siri and Cortana, making use of the French Discourse Analysis method. From the interaction with the assistants and comparison of their responses with those found in previous surveys, it was identified the discursive formations and the ideological formations in such speech, aiming to find stereotypic patterns. By working on the identification of unconscious gender biases in the discourse, approaching Human-Computer Interaction, it is noted how the prejudice-laden patriarchal culture presents itself in mediation with technology. Analyzing the assistant’s answers to gender-related interactions, an awareness can be developed to help with a strategy of technological solutions that adjust this experience and create a less harmful and more inclusive design.